Mini-Review: Mixed Ionic–Electronic Charge Carrier Localization and Transport in Hybrid Organic–Inorganic Nanomaterials - Romero, Mariano; Mombrú, Dominique; Pignanelli, Fernando; Faccio, Ricardo; Mombrú, Alvaro W. (Frontiers in Chemistry, 2020)
In this mini-review, a comprehensive discussion on the state of the art of hybrid organic–inorganic mixed ionic–electronic conductors (hOI-MIECs) is given, focusing on conducting polymer nanocomposites comprising inorganic nanoparticles ranging from ceramic-in-polymer to polymer-in-ceramic concentration regimes. First, a brief discussion on fundamental aspects of mixed ionic–electronic transport phenomena considering the charge carrier transport at bulk regions together with the effect of the organic–inorganic interphase of hybrid nanocomposites is presented. We also make a recount of updated instrumentation techniques to characterize structure, microstructure, chemical composition, and mixed ionic–electronic transport with special focus on those relevant for hOI-MIECs. Raman imaging and impedance spectroscopy instrumentation techniques are particularly discussed as relatively simple and versatile tools to study the charge carrier localization and transport at different regions of hOI-MIECs including both bulk and interphase regions to shed some light on the mixed ionic–electronic transport mechanism. In addition, we will also refer to different device assembly configurations and in situ/operando measurements experiments to analyze mixed ionic–electronic conduction phenomena for different specific applications. Finally, we will also review the broad range of promising applications of hOI-MIECs, mainly in the field of energy storage and conversion, but also in the emerging field of electronics and bioelectronics.